Creating Acceptable Tablets 3D (CAT 3D): A Feasibility Study to Evaluate the Acceptability of 3D Printed Tablets in Children and Young People - Louise Bracken; Rober Habashy; Emma McDonough; Fiona Wilson; Joanne Shakeshaft; Udeme Ohia; Tamar Garcia-Sorribes; Abdullah Isreb; Mohamed A. Alhnan; Matthew Peak (MDPI AG, 2022)
3D printing (3DP) has been proposed as a novel approach for personalising dosage forms for children and young people (CYP). Owing to its low cost and the lack of need for finishing steps, fused deposing modelling (FDM) 3DP has been heavily researched in solid dosage forms (SDFs) manufacturing. However, the swallowability and overall acceptability of 3D printed dosage forms are yet to be established. This work is the first to evaluate the acceptability of different sized 3D printed placebo SDFs in CYP (aged 4-12 years). All participants had previously participated in a feasibility study (CAT study) that assessed the swallowability and acceptability of different sized GMP manufactured placebo conventional film-coated tablets, and therefore only attempted to swallow one 3D printed tablet. The participants assessed the swallowability, acceptability, mouthfeel, volume of water consumed, and taste of the sample using a 5-point hedonic facial scale on a participant questionnaire. A total of 30 participants were recruited, 87% of whom successfully swallowed the 3D printed tablet that they attempted to take. Attributes of the 3D printed tablets were scored as acceptable by the following percentage of participants-swallowability (80%), mouthfeel/texture (87%), the volume of water consumed (80%), taste (93%), and overall acceptability (83%). Overall, 77% of children reported they would be happy to take the tablet every day if it was a medicine. Participants were also asked which tablets felt better in the mouth-the film-coated tablets or the 3D printed tablets, and the most popular response (43%) was that both were acceptable. This study shows that FDM-based 3D printed SDFs may be a suitable dosage form for children aged 4-12 years. The results from this feasibility study will be used to inform a larger, definitive study looking at the acceptability of 3D printed tablets in children.